Exploring the formation dynamics of affective polarization by considering coupled feedback - Cui, Peng-Bi (Frontiers in Physics, 2023)
Polarization issues are generally subject to ideological and affective polarization. Particularly, affective polarization generally accelerates the polarization process. Yet, a wide array of the existing literature has not provided valid ways to make distinctions between them. Therefore, the mechanism contributing to the rise of affective polarization still remains unclear, along with its unique emergent dynamics. To address this issue, we introduces the coupled feedback between opinions and response susceptibility to an attraction–repulsion model which takes into account three parameters: interaction strength, response susceptibility, and tolerance to others. The model features phase diagrams of global consensus, affective polarization, and “harmony with diversity” states. Subsequently, we proceed simulations on time-varying and static social networks, showing that intermediate parameter ranges yield a global consensus as one integrated cluster collapsing and converging toward an uncertain moderate position after long-term persistence. The feedback essentially offers a counterforce to establish an inversion between the global consensus and “harmony with diversity”. Remarkably, strengthening feedback may facilitate polarization by driving the system to first self-organize into one integrated cluster, which then gradually approaches polarization, especially for low tolerance and strong interactions, whereby the step-like dynamic behaviors of opinion entropy suggest the occurrence of a dynamic equilibrium. In summary, the aforementioned phenomena have never been unearthed before and can be regarded as unique dynamics features of affective polarization. Finally, this study attempts to offer a useful approach to the micro foundations of affective polarization for the first time, and the results guide us on how to avoid the dilemmas of this polarization.